Postoperative cerebro spinal fluid diversion in patients with third ventricular colloid cysts - Ahmer Nasir Baig; Syeda Kubra Kishwar Jafri; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2022)
Colloid cysts are a group of CNS neoplasms that usually present with features of CSF flow obstruction. The treatment is by microsurgical, endoscopic or stereotactic techniques. Hydrocephalus usually resolves postoperatively, but in around 3-7% of cases symptoms persist and ultimately require CSF diversion. Several factors such as operative approach, cyst size, operative time, intraoperative bleeding may influence the need for CSF diversion but most of these are yet to be statistically proven. Existing literature is mainly focused on incidence of CSF diversion after resection of colloid cyst rather than the factors which may predict its necessity and extensive research is required to accurately determine these factors. Keywords: Colloid cyst, third ventricle, Cerebrospinal fluid diversion.